Recovery of bone microarchitecture and density four years after spaceflight: two case studies - Bryn E. Matheson; Matthias Walle; Anna-Maria Liphardt; Paul A. Hulme; Martina Heer; Sara R. Zwart; Jean D. Sibonga; Scott M. Smith; Leigh Gabel; Steven K. Boyd (npj Microgravity)
Abstract Spaceflight is known to negatively impact bone health, but the duration of these effects remains unclear. These two case studies investigated bone microarchitecture, density, and remodelling up to 4 years after long-duration spaceflight, aiming to inform countermeasure development and guide future research efforts. High-resolution peripheral quantitative computed tomography (HR-pQCT) and dual X-ray absorptiometry (DXA) scans were conducted on two crew members at pre-flight and up to 48-months post-spaceflight. Both crew members exhibited significant bone loss in the tibia at return from spaceflight, while only one crew member showed losses in the radius. After 4 years of recovery, one crew member achieved full recovery, while the second experienced persistent trabecular deficits that were compensated by significant cortical thickening. These results provide insight into the need for tailored countermeasures and prolonged monitoring to optimize skeletal health for future long-duration space missions, with implications for bone health research on mechanical unloading and reloading.